Modelling the effect of passive representation and intersectionality on perceived bureaucratic discrimination - Eva Thomann; Carolin Hjort Rapp; Katharina Ziegler; Jana Gómez Díaz (University of Konstanz, Cluster of Excellence "The Politics of Inequality", 2024)
This research note sets out to draw up a research agenda on the role of passive representation and intersectionality for perceived bureaucratic discrimination, emphasizing the need to open the discussion on how to model intersectionality and improve the measurement of subjective discrimination. The research note draws on the illustrative example of education, which is one of the earliest and most prominent places where individuals experience discrimination. Street-level bureaucrats, such as teachers, play a pivotal role in delivering public services and ensuring equal rights, yet biased behaviors based on characteristics like ethnicity and gender persist. This research builds on representative bureaucracy theory, which posits that a diverse staff reflective of the population can mitigate discrimination, but introduces the complexity of intersectionality-the idea that individuals belong to multiple social groups, impacting their experiences of discrimination uniquely. 2 Through an exploratory online survey conducted among social science students at the University of Konstanz, the study investigates the combined effects of multiple overlapping identities of students and teachers on experiences of discrimination in schools. The survey captures various dimensions of perceived unfair treatment, including assessment, punishment, and support. Findings indicate that students with a migration background, particularly males, experience higher levels of discrimination. While gender-based discrimination is less evident, female representation among teachers appears to reduce discrimination for female students. However, overall teacher diversity does not significantly impact perceived discrimination. The research note underscores the importance of considering intersectionality in understanding bureaucratic discrimination in future research and suggests that merely increasing diversity among teachers is insufficient. Effective representation and attention to student intersectionality are crucial for addressing discrimination, highlighting the need for targeted strategies to support vulnerable groups. Future research should include more diverse samples and contexts to further explore these complex patterns.
urn:nbn:de:bsz:352-2-1mfavmn3suem2
Keywords: 320; Bureaucratic discrimination; intersectionality; passive representation; representative bureaucracy